FRI0322 Diagnostic accuracy of new american college of rheumatology classification criteria for sjogren's syndrome of 2012. (23rd January 2014) - Milic, V. D.; Radunovic, G.; Damjanov, N.
Abstract : Background: The American-European Classification Criteria (AECC) for Sjogren's syndrome (SS) of 2002 include the six items: I) symptoms of ocular and II) oral dryness, III) objective evidence of dry eyes (abnormal Schirmer's test or Rose Bengal test), IV) objective evidence of salivary gland involvement (abnormal salivary flow rate, parotid sialography or sialoscintigraphy), V) positive biopsy minor salivary gland (MSG) and VI) presence of anti-SS-A/SS-B autoantibodies. The AECC requires four of six criteria, including the biopsy or autoantibody criterion. The new American College of Rheumatology (ACR) Classification Criteria for SS published in 2012 requires at least 2 of the following 3 objectives criteria: I) positive anti-SS-A/SS-B antibody or (positive rheumatoid factor and antinuclear antibody titer ≥1/320), II) abnormal Rose Bengal test with ocular staining score ≥3 or III) positive biopsy of MSG (focus score≥1/4mm² of glandular tissue). Objectives: To assess the diagnostic accuracy of new ACR Classification Criteria for SS of 2012 and compare to previous AECC of 2002. Methods: The study evaluated subjects with suspected SS referred to Institute of Rheumatology, Belgrade. Written consent was obtained from all subjects and the study was approved by the local medical ethics committee. All subjects underwent a full diagnostic workup for SS. Besides the questionnaire, the patients were subjected to a objective criteria for SS: Schirmer-I test, Rose-Bengal score determination, serological tests (rheumatoid factor, antinuclear antibody, anti-SS-A/SS-B antibodies), sialoscintigraphy and biopsy of MSG. The patients (pts) with SS according to the AECC were clasiffied as AECC-SS pts, while pts with SS according to the ACR Classification Criteria as ACR-SS pts. Statistical analyses were performed using SPSS 16.0. The diagnosis accuracy of each set of criteria was evaluated by area under receiver operating characteristics (AUC ROC). "Gold standard" for diagnosis of SS is the positive of ≥ 4 objective criteria of SS (Schirmer-I test, Rose-Bengal score determination ≥3, rheumatoid factor and antinuclear antibody ≥1/320, anti-SS-A/SS-B antibodies, sialoscintigraphy or biopsy of MSG). We exluded symptoms of ocular and oral dryness. Results: The study group included 231 subjects, the mean±SD age 56.1±12.7 years, female/male 225/6, the mean ± SD symptoms duration 3.75±4.0 years. Out of 231 examined, a 150 (65%) pts fulfilled the AECC for the diagnosis of SS, while 129 (56%) patients fulfilled the ACR Classification Criteria for SS. Among 150/231 AEC-SS pts, 111 (74%) pts met ACR Classification Criteria for SS. In the remaining 81/231 subjects wich not fulfilled the AECC, 18 (22%) pts met the criteria defined as ACR Classification Criteria. Diagnostic accuracy of ACR Classification Criteria was better than AECC (AUC-ROC±S.E. for the ACR was 0.87±0.02, followed by AECC 0.83±0.03). The new ACR Classification Criteria for SS had much higher specificity than the AECC (92.7% versus 78.0%). Sensitivity of ACR Classification Criteria was slightly less than the AECC (82.6% versus 87.9 %). Conclusions: Our results suggest higher diagnostic accuracy of new ACR Classification Criteria for SS of 2012 than previous AECC of 2002. Further studies in a larger cohort of patients with suspected SS are necessary. Disclosure of Interest : None Declared